Feasibility of Near‐Real‐Time GOLD Data Products. Issue 6 (13th June 2020) - Codrescu, S. M.; Rowland, W. F.; Plummer, T. M.; Vanier, B. A.; Berger, T. E.; Codrescu, M. V.
Abstract: A primary limitation for accurate specification and forecasting of the thermosphere‐ionosphere (TI) system is uncertainty in the system forcing. This significantly impacts users who have operational and real‐time interests in the current and future state of the TI system. Since Global‐Scale Observations of the Limb and Disk (GOLD) observations are expected to provide information about both the current state and forcing of the TI system, GOLD products could be an operational asset if they could be provided in near real time. Production of GOLD data products requires knowledge of the satellite pointing and location. The current scientific processing implementation contains an operationally significant delay to await definitive location and as‐flown pointing. We present the results of a demonstration low‐latency processing system that assumes the nominal satellite position and pointing to produce low‐latency GOLD data products. The resulting products are reasonably similar to the scientific version but are available within minutes rather than hours. Plain Language Summary: The Global‐Scale Observations of the Limb and Disk (GOLD) mission is a research mission that observes the upper atmosphere. Normally, at some point after the observations are made, scientists will analyze them. However, there are users who would benefit from near‐real‐time access to these data since they are expected to give a comprehensive picture of current space weather in the low Earth orbit (LEO) environment. This information would be of interest to someone who is flying a satellite in this region, for example. This article explores the possibility of processing GOLD data in near real time. The normal data processing includes a significant 2‐hr delay waiting to receive the exact satellite position and pointing. This article shows that it is possible to remove most of the delay by assuming the satellite is at its normal location and pointing straight down. This assumption produces small but acceptable changes to the resulting data yet makes the data available while they are still relevant to real‐time users. Key Points: Near‐real‐time GOLD data can be useful for operational and real‐time users Near‐real‐time GOLD data can be produced with a latency of 10–20 min by assuming nominal instrument pointing and satellite position Near‐real‐time GOLD data products are reasonably similar to the science products produced with definitive geolocation